PENGARUH MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PT. FIF CURUP - Gilang Ramadhan; Islamuddin Islamuddin (UM. Bengkulu, 2023)
Given the importance of employee motivation, work motivation is one of the factors that need attention from company leaders. Problem formulation 1) Is there any influence of work motivation on employee performance of PT. FIF Curup? 2) Is there any influence of the work environment on the performance of employees of PT. FIF Curup? 3) Is there any influence of work motivation and work environment on the performance of employees of PT. FIF Curu This study aims 1) To determine the effect of work motivation on the performance of employees of PT. FIF Curup 2) To determine the effect of the work environment on the performance of employees of PT. FIF Curup? 3) To determine the effect of work motivation and work environment on the performance of employees of PT. FIF Curup. This type of research is a quantitative approach. The method used in this research is descriptive method. The population in this study were all employees at PT. FIF Curup has 35 employees. a sample of 35 people PT. FIF Curup. Based on the results of research on the influence of work motivation and work environment on employee performance at PT. FIF Curup. The tSig value for the work motivation variable (X1) is 0.002. So it can be concluded that tSig<Sig (0.002<0.050 ) means that Ha is accepted and H0 is rejected, that the variable of work motivation affects the performance of employees of PT. FIF Curup. The tSig value for the work environment variable (X2) is 0.001. So it can be concluded that tSig<Sig (0.001<0.050 ) means Ha is accepted and H0 is rejected, that the work environment variable affects the performance of employees of PT. FIF Curup. The hypothesis test above can be seen for the variable work motivation (X1), and work environment (X2) the value of Fsig = 0.004. So it can be concluded that FSig < Sig (0.004 < 0.050 ) means Ha is accepted and H0 is rejected, that each variable has a significant effect on employee performance (Y) at PT. FIF Curup. Keywords: Work Motivation, Work Environment, Employee Performance,